PENGARUH PENERAPAN PRINSIP GOOD CORPORATE GOVERNANCE (GCG) TERHADAP PENINGKATAN KUALITAS PELAYANAN DI PT BANK BTPN TBK CABANG PADANG - Dewi Dahlan (Alfuad: Jurnal Sosial Keagamaan, 2018)
This study aims to determine the effect of the principles of good corporate governance (GCG) in this case transparency, accountability, responsibility, independence, and fairness towards service quality at the Padang branch of PT Bank BTPN Tbk. The results of this study indicate that Good Corporate Governance (GCG) (X) has a significant effect on the Service Quality of Padang Branch BTPN Banks (Y). The contribution of Good Corporate Governance (X) to Service Quality (Y) is 79.9% and found to have a significant effect, while the remaining 20.1% is another factor not examined. The most powerful dimension of correlation is transparency with a correlation value of 0.896. All dimensions of service quality including tangible, reliability, responsiveness, assurance, and empathy have a strong correlation with Service Quality (Y), and are significant. The strongest correlation dimension is Reliability with a correlation value of 0.900.